Les sonorités vocaliques, éléments submorphémiques du discours musical en poésie - Michel Barrucand (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2012)
The academic stylistic analysis of the poem is located at several levels: the general themes, the word choice, the meaning of words, the syntax organization, the rhetoric of images, their logical linking, but also what Suhamy calls “ the art of speech”, in other words, the inner poetical music. This “submorphemic” level, defined by the sounds within the poetical language (onomatopoeia, alliterations, assonances, paronomases) can be considered as a logistic basis on which the creation of the poem is set up, which is shown by the study of poets’ manuscripts. However, a rigorous approach, both synthetic and diachronic, of inner sound phenomena, can enable the researcher to bring complex musical patterns into focus, and to compare them with the arrangements of musical modules on a musical staff, consequently revealing melodic lines. In other words, the poem can be considered as a musical score. Because of the complexity of the sound phenomena in American English, we will mainly pay attention to the series of vocalic sounds. By analysing, thanks to appropriate synoptic charts, the recurrence of the vocalic sounds in a corpus of American poems written in the 19th century by poets largely influenced by music (E. Poe, W. Whitman) or themselves musicians (W. Longfellow, S. Lanier, E. Dickinson), we will show that the musical structure of the poem can reveal melodic lines built according to the laws of classical musical composition, melodies which participate actively in the semantic definition of the poem and its comprehension by a curious and attentive reader.